2013
DOI: 10.1155/2013/134813
|View full text |Cite
|
Sign up to set email alerts
|

An Active C-Terminally Truncated Form of Ca2+/Calmodulin-Dependent Protein Kinase Phosphatase-N (CaMKP-N/PPM1E)

Abstract: Ca2+/calmodulin-dependent protein kinase phosphatase (CaMKP/PPM1F) and its nuclear homolog CaMKP-N (PPM1E) are Ser/Thr protein phosphatases that belong to the PPM family. CaMKP-N is expressed in the brain and undergoes proteolytic processing to yield a C-terminally truncated form. The physiological significance of this processing, however, is not fully understood. Using a wheat-embryo cell-free protein expression system, we prepared human CaMKP-N (hCaMKP-N(WT)) and the truncated form, hCaMKP-N(1–559), to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…PPM1E appears to be a protein phosphatase that specifically dephosphorylates and regulates multifunctional calcium and Calmodulin-regulated kinases but unique in that it localizes the nucleus (hence, -N). Ishida et al 20 found that by using gene knockdown studies in zebrafish, they were able to conclude that this enzyme was essential for the early development of the brain and spinal cord. As the pattern of expression for PPM1E was fairly intense and specific for CA1, further research on the functional role this enzyme may play in hippocampal physiology overall with specific inquiry to any possible role in memory formation.…”
Section: Resultsmentioning
confidence: 99%
“…PPM1E appears to be a protein phosphatase that specifically dephosphorylates and regulates multifunctional calcium and Calmodulin-regulated kinases but unique in that it localizes the nucleus (hence, -N). Ishida et al 20 found that by using gene knockdown studies in zebrafish, they were able to conclude that this enzyme was essential for the early development of the brain and spinal cord. As the pattern of expression for PPM1E was fairly intense and specific for CA1, further research on the functional role this enzyme may play in hippocampal physiology overall with specific inquiry to any possible role in memory formation.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Ishida et. al with a C-terminally truncated version of POPX1 (1-559) found that the proteolytic processed version of POPX1 exhibit higher phosphatase activity compared to the full length, suggesting that the proteolytic processing of POPX1 at the C-terminal serves as a post-translational regulatory mechanism to generate a highly active phosphatase (Ishida et al, 2013). The PP2C phosphatase domain in grey.…”
Section: Additional Taz Regulationsmentioning
confidence: 99%